Optimization of the root canals preparation in accordance with their anatomy (Эндодонтия Today, 2020)
Dental radiographs used in endodontic therapy are two-dimensional (2D) and do not provide full information on the tooth cavity. In recent years the investigation of patients with disorders of the teeth and jaws are increasingly using dental computed tomography. When comparing the anatomical topography of the tooth extraction and its image into 3D CT revealed that the topography of the root canal is transferred reliably enough to make a decision on the choice of the method of preparation and obturation. Investigated tooth removed and created endodontic access. Extracted tooth was treated by the procedure, which can make it transparent. The proposed method of visualization of the root canals of teeth makes possible a detailed analysis of the anatomy of the root canal, while maintaining its anatomical shape and size, which is important in the learning process.